The Effect of Digital Media and Visual-Spatial Intelligence on Geometry Learning Outcomes for Grade 4 Elementary Students - Nurmida Catherine Sitompul; I Nyoman Sudana Degeng; Hendra Wahyu Riyanto; Sri Rahmawati Fitriatien (International Journal of Learning Reformation in Elementary Education, 2026)
E-books and G-Sites are increasingly commonly used in geometry learning in elementary schools; therefore, it is necessary to conduct more intensive research to ensure the effectiveness of this digital media in accordance with the characteristics of students.  This study investigated the effect of these media on Grade 4 students who have different levels of visual-spatial intelligence on their understanding of the subject of geometry. The study employed a quasi-experimental method with a 2x2 factorial design, pretest-post-test. The research subjects were 62 students.  This study showed that (1) G-Sites is significantly more effective than e-books in improving geometry learning; (2) students who have high visual-spatial intelligence have a better understanding of geometry than those who have low visual-spatial intelligence; and (3) there is an interaction between digital media and students’ visual-spatial intelligence on the understanding of geometry.  G-Sites are a significantly more effective medium for students with low visual-spatial intelligence.  The conclusion is that the use of digital media for geometry material should consider students’ visual-spatial intelligence.  We suggest that the use of e-books should be combined with concrete media. Concrete media can facilitate the process of externalization from 2D representation to 3D understanding, thereby reducing the cognitive load experienced by low-visual-spatial students.  It is necessary to conduct research by considering other characteristics of students.